From nanomaterials to macromolecules: Innovative technologies for latent fingerprint development. Issue 2 (27th November 2022) - Assis, Alexandro M. L.; Costa, Cristiane V.; Alves, Meclycia S.; Melo, Jeane C. S.; de Oliveira, Vitória R.; Tonholo, Josealdo; Hillman, A. Robert; Ribeiro, Adriana S.
Abstract: The majority of conventional techniques for latent fingerprint enhancement are based on chemical reactions or interactions between the developer and fingermark residue components, providing contrast between the surface and the fingerprint ridges. However, these methods might be limited by factors associated with particle size, toxicity of the reagent, selectivity, or sensitivity, that may be circumvented by the synthetic design of innovative materials based on nanoparticles or macromolecular materials, such as conducting polymers, applied as latent fingerprint developers on different surfaces and conditions. Since the structural, optical and electronic properties of the material can be tailored by its molecular scale, the size control of the developer plays an important role to improve the interaction with the latent fingermark residue and/or the surface, enhancing the color contrast and the quality of the developed image (or dactylogram). Hence, creating new reagents and strategies to apply nano‐ and macromolecular scale materials as latent fingermark developers constitutes an exciting rapidly expanding area, generating a wealth of new materials that lead to forensic methodologies with enhanced performance. Recent progress in the application of such materials for development of latent fingermarks present on different surfaces and subject to complex circumstances will be discussed. This will focus on the main barriers to making nanoparticles and conducting polymers viable—and occasionally preferred—materials routinely used by forensic experts, and the potential advantages over conventional methodologies in the acquisition and analysis of crime scene evidence. This article is categorized under: Forensic Chemistry and Trace Evidence > Trace Evidence Forensic Chemistry and Trace Evidence > Fingermarks and Other Marks Forensic Chemistry and Trace Evidence > Emerging Technologies and Methods Abstract : Nanoparticles and conjugated polymers provide combinations of physical size and chemical specificity that can be synthetically manipulated to bind selectively with either fingermark residue or substrate, revealing latent fingermarks with high contrast and spatial definition.